Characteristics of constructive interaction of younger pupils with the peers - Kruglova, Nadezhda V. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The research is devoted to the study of the characteristics of constructive interaction between primary schoolchildren and peers in the process of joint problem solving. Children with a high level of constructive interaction are more inclined to show altruism in solving a joint problem for both preferred and rejected children; have significantly stronger motivation of helping behaviour towards rejected children and significant tendency to help preferred peers; have more significant cooperative orientation of communication and a tendency to choose a constructive strategy for making a common decision. Significant positive correlations between indicators of constructive interaction and motivation of helping behaviour, altruism to both the preferred and the rejected children, motivation of activity, cooperative orientation of communication and a constructive strategy for making a common decision established. A significant negative correlation was found between the indicators of constructive interaction and egoism to the preferred child.
Keywords: constructive interaction; motivation of helping behaviour; altruism; egoism; helping behaviour; motivation of activity; result of activity; cooperative orientation of communication; constructive strategy for making a common decision; strategy of activity